Exploring the Legitimacy Construction of the Pharmaceutical Industry from a Communication View on Corporate Social Responsibility - Mariana Arellano, Mariana (2015)
The current dissertation adopts the recently developed communication view on Corporate Social Responsibility (CSR), which frames the exploration of legitimacy construction of the pharmaceutical industry in the network society. In line with this view, polyphony of CSR and communicative dynamics within social media networks are necessary for the legitimation process (Schultz et al., 2013; Castelló et al., 2013).